G13-mediated signaling pathway is required for pressure overload-induced cardiac remodeling and heart failure - Takefuji, Mikito; Wirth, Angela; Lukasova, Martina; Takefuji, Seiko; Böttger, Thomas; Braun, Thomas; Althoff, Till F.; Offermanns, Stefan; Wettschureck, Nina (Circulation, 2012)
Background—Cardiac remodeling in response to pressure or volume overload plays an important role in the pathogenesis of heart failure. Various mechanisms have been suggested to translate mechanical stress into structural changes, one of them being the release of humoral factors such as angiotensin II and endothelin-1, which in turn promote cardiac hypertrophy and fibrosis. A large body of evidence suggests that the prohypertrophic effects of these factors are mediated by receptors coupled to the Gq/11 family of heterotrimeric G proteins. Most Gq/11-coupled receptors, however, can also activate G proteins of the G12/13 family, but the role of G12/13 in cardiac remodeling is not understood. - Methods and Results—We use siRNA-mediated knockdown in vitro and conditional gene inactivation in vivo to study the role of the G12/13 family in pressure overload-induced cardiac remodeling. We show in detail that inducible cardiomyocyte-specific inactivation of the α subunit of G13, Gα13, does not affect basal heart function but protects mice from pressure overload-induced hypertrophy and fibrosis as efficiently as inactivation of Gαq/11. Furthermore, inactivation of Gα13 prevents the development of heart failure up to 1 year after overloading. On the molecular level, we show that Gα13, but not Gαq/11, controls agonist-induced expression of hypertrophy-specific genes through activation of the small GTPase RhoA and consecutive activation of myocardin-related transcription factors. - Conclusion—Our data show that the G12/13 family of heterotrimeric G proteins is centrally involved in pressure overload-induced cardiac remodeling and plays a central role in the transition to heart failure.
Im Titel ist die Zahl 13 tiefgestellt
Gesehen am 04.07.2018